Students' Critical Thinking and Mathematical Problem Solving Skills through the Problem Based Learning (PBL) Model and Guided Inquiry at SMA Negeri 5 Lebong - Dahliah, Jeli; Fitriani, Apriza; Risnanosanti, Risnanosanti (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to determine whether there are differences and influences on students' critical thinking and mathematical problem-solving abilities through the Problem Based Learning (PBL) and Guided Inquiry models at SMA Negeri 5 Lebong. The population of this study was all grade X students of SMA Negeri 5 Lebong. The sampling technique used cluster random sampling, namely random sampling based on class, so that three sample classes were obtained, each consisting of 33 students, namely class X.1, X.2, and X.5 with a total of 99 students. The type of research used was quasi-experimental. Data collection was carried out using essay tests to measure students' critical thinking and mathematical problem-solving abilities. Data were analyzed using the One Way ANOVA test. The results of the study showed that there were significant differences in students' critical thinking and mathematical problem-solving abilities between classes using the PBL, Guided Inquiry and Conventional Learning models. The Guided Inquiry model was more effective in improving critical thinking abilities and the PBL model showed more effectiveness in improving students' mathematical problem-solving abilities.